Living Along Distribution Margins: Differences in the Body and Biochemistry of Red Squat Lobster Morphotypes (Grimothea monodon) from the Humboldt Current System - Marco Quispe-Machaca; Maximiliano Zilleruelo; Pepe Espinoza; Gabriela Torres; Ángel Urzúa (Fishes, 2024)
Grimothea monodon, an important fishery resource in the Humboldt Current marine ecosystem (HCE), present two contrasting morphotypes (PM, pelagic morphotype; BM, benthic morphotype). The fishery management of G. monodon is focused on understanding only fishery aspects that apply to a limited area, and there are currently no studies that evaluate the nutritional status of these morphotypes. This study evaluated the biological performance of PM and BM, analyzing the body (size, CL; weight, W; condition factor, Kn) and biochemical condition (glucose, G; proteins, P; lipids, L; fatty acids, FAs). The results reveal that G. monodon showed differences in CL and W between morphotypes, with higher values in BM than PM. The Kn was different between morphotypes with a tendency of isometric growth. In turn, the G contents were higher in PM than BM, while the contents of P, L, and FAs showed an opposite tendency, with higher contents recorded in BM than PM. Our findings suggest that the Kn should be included to strengthen the biological parameters and their relationships used in fishery management models. Differences in the biochemical condition between morphotypes can be considered potentially adaptive, in response to the combined effect of environmental factors that vary in the HCE.